2016
DOI: 10.1515/revce-2015-0038
|View full text |Cite
|
Sign up to set email alerts
|

Emerging trends in graphene carbon based polymer nanocomposites and applications

Abstract: Recent sustainable advancement in carbon nanotechnology has further broadened the scope of application of carbon based materials, especially graphene based polymer nanocomposites, in emerging applications. This paper mainly focuses on recently emerging trends in synthesis and properties of graphene based polymer nanocomposites, in addition to brief discussion of some selected carbon based nanocomposites for application in electromagnetic interference shielding efficiency, terahertz shielding efficiency, electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(28 citation statements)
references
References 71 publications
0
28
0
Order By: Relevance
“…Electrical conductivity enables materials to be utilized in electronic devices or as conducting membranes for sensor application 124,125 . The electrical conductivity of PPy is influenced by several crucial factors, such as type of oxidants, initial O/M, dopants or surfactants, polymerization temperature, and polymerization time 126‐128 .…”
Section: Factors Affecting Ppy Conductivitymentioning
confidence: 99%
“…Electrical conductivity enables materials to be utilized in electronic devices or as conducting membranes for sensor application 124,125 . The electrical conductivity of PPy is influenced by several crucial factors, such as type of oxidants, initial O/M, dopants or surfactants, polymerization temperature, and polymerization time 126‐128 .…”
Section: Factors Affecting Ppy Conductivitymentioning
confidence: 99%
“…Improved flexural properties for composites loading are ascribed to high stiffness and aspect ratio of graphene sheets. 28 In addition, increment in flexural properties was anticipated as a result of enhanced adhesion between components in the composites. A study has reported that the modulus of nanocomposites at elevated GNP loading may not increase due to agglomeration of GNP sheets.…”
Section: Resultsmentioning
confidence: 99%
“…The scope of nanoscience and nanotechnology has provided nanocomposites materials with superior properties to be used in industrial and technological development for a wide range of devices. Carbon-based polymer nanocomposites provide a wide spectrum of opportunities to produce novel multifunctional materials individually and on hybridization for applications in thermal materials, electromagnetic interface shielding, sensors, and energy storage [107].…”
Section: Applications Of Carbon-based Polymer Nanocompositesmentioning
confidence: 99%